2009
DOI: 10.1111/j.1399-0039.2009.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 gene polymorphisms and soluble CTLA4 protein in Behcet’s disease

Abstract: Cytotoxic T lymphocyte antigen 4 (CTLA4; CD152) is a costimulatory molecule expressed on activated T cells that plays a key inhibitory role during T lymphocyte activation. The gene encoding for CTLA4 has been suggested as a candidate for conferring susceptibility to autoinflammatory diseases. We investigated the polymorphisms of the CTLA4 gene [promoter region (21722 T/C, 21661 A/G and 2318 C/T) and exon 1 (149 G/A)] and the differences of serum soluble sCTLA4 levels in 285 patients with Behcet's disease (BD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…Meanwhile, our results disagree with the meta-analysis study of Lee and Song et al [21] and Zhang et al [22] as well as with multiple previous studies conducted on different ethnic populations like Chinese [23], Korean [24], and UK and Middle East populations [25]. This inconsistency may be due to the racial/ethnic differences in allele frequencies, population differences, environmental factors (microbial loading), and limited number of study participants or due to the wide differences of the clinical manifestations in BD patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, our results disagree with the meta-analysis study of Lee and Song et al [21] and Zhang et al [22] as well as with multiple previous studies conducted on different ethnic populations like Chinese [23], Korean [24], and UK and Middle East populations [25]. This inconsistency may be due to the racial/ethnic differences in allele frequencies, population differences, environmental factors (microbial loading), and limited number of study participants or due to the wide differences of the clinical manifestations in BD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, there were significantly decreased sCTLA-4 concentrations in BD patients in comparison to the controls being in concordance with Park et al [24] who found that the mean serum sCTLA-4 concentration in BD patients was significantly lower than that in controls, concluding that decreased level of sCTLA-4 might result in enhanced activation and proliferation of T cells, which could lead to the development of chronic inflammatory diseases like BD [24]. However, this result is partially contradictory to that of Sim et al [27] who reported a reduced expression of CTLA-4 in CD4+ T cells in patients with active Behçet's disease, with no difference in the production of sCTLA-4, leading to subsequent increase in Th1 cell proliferation and a tendency to the development of Behçet's disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data have shown lower levels of flCTLA4 and sCTLA4 mRNA in biopsies of inflamed colonic tissue obtained from UC patients. Our findings are similar with those of several recent reports, which showed that the flCTLA4 protein and sCTLA4 mRNA levels were decreased in myasthenia gravis patients, 29,41 and sCTLA4 protein levels were decreased in individuals with diabetes, Behcet's disease and abdominal aortic aneurysm; [42][43][44] however, Wong et al 45 have shown increased levels of the sCTLA4 protein in systemic lupus erythematosus. Possible mechanisms producing different levels of sCTLA4 levels in autoimmune diseases could be: (1) stimulation of T lymphocytes results in significantly decreased expression of sCTLA4, 15 (2) there are cell types other than T cells expressing CTLA4, for example, skeletal muscle cells and granulocytes, 46,47 which also may express sCTLA4 and secrete into serum, (3) protein levels are affected not only by mRNA levels; and (4) differential sCTLA4 levels may correlate with different CTLA4 genotypes, disease types and immunological states.…”
Section: Ctla4 Gene Polymorphisms In Ucsupporting
confidence: 92%
“…Yousefipour et al (20) detected that this polymorphism was associated with susceptibility to multiple sclerosis in Iranian population. Park et al (21) found this polymorphism to be significantly higher in patients with Behçet's disease compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%